Preaching God's word : a hands-on approach to preparing, developing, and delivering the sermon /: a hands-on approach to preparing, developing, and delivering the sermon. (2018) - Carter, Terry G; Duvall, J. Scott; Hays, J. Daniel, 1953-
No abstract available